UiTM Swimming Pool Complex / Mohd Qaedi Fazi Abd Aziz, Nur Aliah Adilla Mohd Asri … [et al.] - ABD AZIZ, MOHD QAEDI FAZI; MOHD ASRI, NUR ALIAH ADILLA; BUNIRAN, NOR SHAFIKA; SAHRIN, NURSYAFIKA; NAHARUDIN, NABILAH (2019)
UiTM Swimming Pool Complex is chosen as the subject in our case study. The company had been established in 1995 and located in Universiti Teknologi MARA (UiTM) Shah Alam. This company provide services such as a built-in swimming pool for the usage of athletes, public and students of UiTM Shah Alam. However, some problems had been identified during the case study process. The registration process took a long time before being proceed as manual registration is done. Plus, the air ventilation in the pool's area is poor as the odor of chlorine is strong. To overcome these problems, two solutions are being suggested to the person-in-charge. A smart club card is being introduced to reduce the time taken for the registration process. The club card contains the information of the members' and the fee can be done through it. Secondly, the installation of Local Exhaust Ventilation (LEV) is recommended as it reduces the air contaminant and less odor of chlorine can be achieved.